2022
DOI: 10.1002/cam4.4728
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pre‐analytical and analytical steps for DNA and RNA analysis of fresh cytology samples

Abstract: Background: Different cytology preparations can be used for molecular diagnostics, however the influence of pre-analytical and analytical steps on the results are not yet well defined. We aimed to determine optimal steps for efficient extraction of DNA and RNA from fresh cells for molecular diagnostics.Methods: MCF7 and FaDu human cell lines, were used as a model to determine fresh cells storage conditions (temperature: 25°C, 4°C, −20°C, −80°C; duration: 0 h, 4 h, 12 h, 24 h, 48 h) and optimal nucleic acids ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A secondary but equally limiting issue is the considerable heterogeneity among laboratories in managing the pre-analytical steps. This factor contributes to reducing even further the already scarce availability of diagnostic samples for the identification of DNA and RNA-based biomarkers [ 25 , 26 ]. In this scenario, harmonization of the analytical procedures is key to achieving timely and accurate analysis of clinically relevant biomarkers starting from very challenging diagnostic specimens [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A secondary but equally limiting issue is the considerable heterogeneity among laboratories in managing the pre-analytical steps. This factor contributes to reducing even further the already scarce availability of diagnostic samples for the identification of DNA and RNA-based biomarkers [ 25 , 26 ]. In this scenario, harmonization of the analytical procedures is key to achieving timely and accurate analysis of clinically relevant biomarkers starting from very challenging diagnostic specimens [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As regards, purification of nucleic acids is another crucial factor to ensure accurate identification of predictive biomarkers [ 26 ]. Of note, we observed that a comparable number of institutions adopted manual and automated technical procedures for DNA and RNA purification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the required tissue volume for NGS has not been determined and depends on the platform used ( 28 , 29 ). As genotyping is highly dependent on cytological preparation, fixation and staining techniques, there are no clear cut-off values, which may reduce reproducibility of these results ( 28 , 30 - 32 ). No additional slides were prepared for MVCA analysis, as we felt this may influence real world results.…”
Section: Discussionmentioning
confidence: 99%